Eye health in farmers: The impact of environmental and occupational factors - Athkar Alawneh; Mohammad Fraiwan; Fidaa Almomani (PLoS ONE, 2025)
Farmers face higher health risks due to constant exposure to environmental and occupational hazards. Prolonged sun exposure increases the risk of UV-related eye damage (e.g., cataracts and pterygium), and frequent contact with dust, pesticides, and airborne debris can lead to chronic eye irritation, infections, and long-term vision problems. The physical demands of farm work, along with limited access to protective eyewear and healthcare, further compound these risks, and make eye health a significant concern in agricultural communities. This cross-sectional study examines the prevalence of eye ailments among farmers, exploring the environmental, occupational, and demographic factors contributing to these conditions. Data were collected from 893 participants and analyzed using a descriptive-correlational methodology to identify associations affecting farmers’ eye health. Individuals whose primary or secondary profession is agriculture reported a greater impact of climate on their eye health (p=0.003), while farmers experienced a more significant effect of agricultural activities on their vision (p=0.007), despite being more likely to use protective equipment. However, no meaningful correlation was found between farming and the prevalence of specific eye illnesses. These findings emphasize that farmers are particularly vulnerable to environmental and occupational factors that negatively impact the daily eye health. Despite their increased use of protective equipment, they still reported significant effects from climate conditions and agricultural activities. This suggests that current protective measures may be insufficient or. inconsistently used. While no direct correlation was found between farming and ipecific eye illnesses, the cumulative impact of environmental exposure on vision health remains a concern. Hence, there is a need for improved protective strategies, increased access to eye care, and targeted interventions to mitigate the occupational risks faced by farmers.